2021
DOI: 10.3390/biomedicines9050569
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Serotonin 5-HT4 Receptors on Responses to Cardiac Stressors in Transgenic Mouse Models

Abstract: The current study aimed to deepen our knowledge on the role of cardiac 5-HT4 receptors under pathophysiological conditions. To this end, we used transgenic (TG) mice that overexpressed human 5-HT4a receptors solely in cardiac myocytes (5-HT4-TG mice) and their wild-type (WT) littermates that do not have functional cardiac 5-HT4 receptors as controls. We found that an inflammation induced by lipopolysaccharide (LPS) was detrimental to cardiac function in both 5-HT4-TG and WT mice. In a hypoxia model, isolated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 63 publications
3
6
0
Order By: Relevance
“…In the present study, the lowest immune function indicators CD4+ and CD8+ levels were found in the observation group, followed by the experimental group, and then the control group ( P < 0.05), suggesting that patients with sepsis are associated with abnormal expression levels of T lymphocytes, which underscores the role of the assay of CD4+ and CD8+ levels for early diagnosis and treatment of sepsis. Moreover, the blood glucose level of patients with sepsis was positively correlated with the levels of IL-6, TNF- α and IL-1 β and was negatively correlated with the levels of CD4+/CD8+; the higher the blood glucose, the lower the number of immune cells, which is in line with the results of the report by Nakamura et al [ 24 ], indicating that the high blood glucose levels are associated with more severe immunity dysfunction in the patients with sepsis. As blood sugar levels increase, IL-6, TNF- α and IL-1 β levels present a trend of increase, whereas the level of CD4+/CD8+ shows a downward trend.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the lowest immune function indicators CD4+ and CD8+ levels were found in the observation group, followed by the experimental group, and then the control group ( P < 0.05), suggesting that patients with sepsis are associated with abnormal expression levels of T lymphocytes, which underscores the role of the assay of CD4+ and CD8+ levels for early diagnosis and treatment of sepsis. Moreover, the blood glucose level of patients with sepsis was positively correlated with the levels of IL-6, TNF- α and IL-1 β and was negatively correlated with the levels of CD4+/CD8+; the higher the blood glucose, the lower the number of immune cells, which is in line with the results of the report by Nakamura et al [ 24 ], indicating that the high blood glucose levels are associated with more severe immunity dysfunction in the patients with sepsis. As blood sugar levels increase, IL-6, TNF- α and IL-1 β levels present a trend of increase, whereas the level of CD4+/CD8+ shows a downward trend.…”
Section: Discussionsupporting
confidence: 90%
“…This was the reason why we have generated H 2 -TG: to study histamine and its action on human H 2 -receptors in a mammalian transgenic heart: only in H 2 -TG but not in WT, histamine exerts a positive inotropic effect. We have confirmed this finding repeatedly (Gergs et al 2019a , b , 2020 ; Neumann et al 2021a , b , c ). As concerns the biochemical basis for these contractile studies, we detected endogenous mouse H 2 -receptors by polymerase chain reaction (PCR) in hearts from WT (Neumann et al 2021c ).…”
Section: Methodssupporting
confidence: 82%
“…1 ). We noted in left atrial preparations from WT that isoproterenol tended to be less potent to raise force of contraction at 23 °C than at 37 °C (Gergs et al 2021a , b , c , d ). Similarly, the effect of histamine on force of contraction in H 2 -TG at 23 °C is located to the right of the curve at 37 °C (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, RNA and protein overexpression of PP2Ac and PP5 are lower in DT than in monotransgenic PP2A or monotransgenic PP5 mice. This effect can be assumed to be specific because in a different double transgenic model, the PP2A mice were crossbred with 5-HT 4 receptor overexpressing mice and in these double transgenic mice, PP2A expression was unchanged compared to the monotransgenic PP2A mice [75]. Hence, some interesting interaction could exist.…”
Section: Discussionmentioning
confidence: 99%